2010
DOI: 10.1158/1078-0432.ccr-09-2574
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Inactivation of PTCH1 Gene in Nevoid Basal Cell Carcinoma Syndrome: Modification of the Two-Hit Hypothesis

Abstract: Purpose: PTCH1 has been identified as the gene responsible for nevoid basal cell carcinoma syndrome (NBCCS). Keratocystic odontogenic tumors (KCOT) are aggressive jaw lesions that may occur in isolation or in association with NBCCS. The aim of this study was to investigate the genetic and/or epigenetic mechanisms of inactivation of the PTCH1 gene in patients with NBCCS and related sporadic KCOTs.Experimental Design: Loss of heterozygosity was analyzed in 44 patients (15 NBCCS-related and 29 sporadic KCOTs), al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 37 publications
(47 reference statements)
3
65
0
2
Order By: Relevance
“…We hypothesize that this rare phenotype likely results from the shortened and nonfunctional truncated PTCH1 protein (p.Asn97LysfxX43), which is expressed from the mutated allele (c.290dupA). To date, more than 80% of reported PTCH1 mutations responsible for NBCCS are nonsense, splice site, insertion, deletion, or duplication mutations that lead to expression of nonfunctional truncated proteins (Boutet et al, 2003;Lo Muzio, 2008), some of which have been confirmed experimentally (Fujii et al, 2003;Pastorino et al, 2005;Pan et al, 2010;Suzuki et al, 2012). These mutations spread along the PTCH1 gene with no preferential hotspot and can arise by several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this rare phenotype likely results from the shortened and nonfunctional truncated PTCH1 protein (p.Asn97LysfxX43), which is expressed from the mutated allele (c.290dupA). To date, more than 80% of reported PTCH1 mutations responsible for NBCCS are nonsense, splice site, insertion, deletion, or duplication mutations that lead to expression of nonfunctional truncated proteins (Boutet et al, 2003;Lo Muzio, 2008), some of which have been confirmed experimentally (Fujii et al, 2003;Pastorino et al, 2005;Pan et al, 2010;Suzuki et al, 2012). These mutations spread along the PTCH1 gene with no preferential hotspot and can arise by several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients harboring PTCH1 deletions of less than 2.4 Mb in size do not exhibit phenotypes atypical for NBCCS. (17,18) To clarify the mechanism underlying the association between heterozygous PTCH1 mutations/deletions and their associated NBCCS-related phenotypic manifestations, two independent lines of Ptch1-deficient mice have been constructed: Ptch1 +/-(exon 1/2) and Ptch1 neo 67/+ mice. (19,20) Both models were found to be prone to tumor development, skeletal abnormalities, and increased susceptibility to irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…23 Most of the malformations are caused by PTCH1 haploinsufficiency, indicating that the physiological pathway activity is sensitive to relatively small changes in PTC1 levels. 19,24 One of the main roles of 5' untranslated region (5'UTR) of mRNAs is post-transcriptional regulation of gene expression, starting from the initiation of protein translation. [25][26][27] The 5'UTRs can differ in length, nucleotide content, secondary structures, and the presence of different functional elements.…”
Section: Introductionmentioning
confidence: 99%